Secure Data Hiding Along Randomly Selected Closed Knight's Tour. Issue 1 (2nd January 2016) - Bansal, Abhishek; Muttoo, Sunil Kumar; Kumar, Vinay
ABSTRACT: A knight may make a move to every square on 8 × 8 chessboards. If we consider a square on a chessboard as vertex and a legal move of a knight from a square to another square as an edge then the path of a knight so traced on a chessboard is a graph. If the knight ends its tour on the square from where it started, then the knight's tour is called closed knight's tour. The numbers of closed knight's tours are 13, 267, 364, 410, 532 in an 8 × 8 chessboard. We may randomly select any one such knight's tour from 13, 267, 364, 410, 532 possible tours for embedding data using fully exploiting modification direction method. Random walk of knight's tour provides a secured data hiding method. Before embedding the secret message, the message is encrypted. Observed embedding results indicate that capacity of the presented method is very high with acceptable Peak Signal to Noise Ratio (PSNR). The approach also provides very good imperceptibility level.